Hyponatremia and 30 days mortality of patients with acute pulmonary embolism - Babak Tamizifar (Journal of Research in Medical Sciences, 2015)
Background: Hyponatremia has poor outcomes in other cardiopulmonary disorders, but its predictive value in predicting mortality of patients with acute pulmonary embolism is unknown. So, we evaluate the mortality of inpatients diagnosed with pulmonary embolism (PE) who had hyponatremia at the time of admission. Materials and Methods: By conducting a cohort study in patients with acute pulmonary embolism admitted in Al-Zahra Hospital during the 24 months of the date of March 2012 to March 2014. We evaluated 224 patients admitted with a primary diagnosis of PE. We used logistic regression analysis to evaluate the independent relation among serum sodium levels at the time of presentation and 30 days mortality, with severity of illness and other patient risk factors were adjusted. Results: 109 patients (48.7%) had normal sodium level (serum level >137 mmol/L). 115 patients had sodium level bellow 137 mmol/L. Of these, 56 (25%) had a sodium level 135-137 mmol/L and 59 (26.3%) had a sodium level <135 mmol/L. Patients with a serum sodium of >137, 135-137, and <135 mmol/L had a cumulative 30-day mortality of 14%, 21%, and 42% (P < 0.0001), respectively. The mortality of patients with lower serum sodium was significantly increased. When the pulmonary embolism severity index and also its simplified form were replaced in the model and while some confounding variables such patients with a history of cancer, chronic pulmonary disease, heart failure, and chronic renal failure were excluded from statistics, the findings still remained similar. Conclusion: Among patients presenting with PE, hyponatremia is common and is an independent risk factor that increasing short-term mortality. This result could be encountered as a variable in determining of PE severity and mortality.